Potential of plantain peels flour (Musa paradisiaca L.) as a source of dietary fiber and antioxidant compound. Issue 1 (2nd January 2016) - Agama-Acevedo, E.; Sañudo-Barajas, J.A.; Vélez De La Rocha, R.; González-Aguilar, G.A.; Bello-Peréz, L.A.
Abstract : Peel from unripe plantain is obtained when the pulp is used for the next production process as starch isolation or dry flour. Plantain peel flour (PPF) was obtained and its chemical composition, composition of the dietary fiber (DF), polyphenol content, antioxidant capacity, and functional properties were studied. PPF had more relevant amounts of protein, ash, total starch, and total dietary fiber (TDF). The main component of DF was the insoluble fraction, with a higher level of cellulose than hemicellulose and lignin. In the insoluble fraction uronic acid was the most predominant acidic monosaccharide, while mannose was in the soluble fraction. Extractable polyphenols were found in the lowest amount, but showed the highest antioxidant capacity. Water- and oil-holding capacity values increased when the temperature of the test increased. The PPF with high DF content, high antioxidant capacity, and functional characteristics could be used as a functional ingredient for the elaboration of food products.